2014
DOI: 10.4013/arq.2014.101.03
|View full text |Cite
|
Sign up to set email alerts
|

Informação de desempenho de um edifício e gráficos de abordagem na concepção de projetos

Abstract: -This research focuses on a new workflow between the fields of Space Layout Planning (SLP) and Building Performance Simulation (BPS) for the early stages of building design with the aim of reducing the energy needs of a building and improving indoor environment quality. Parameters of environmental performance requirements, such as temperature, view, acoustics, and so forth, were selected from different international standards. The intention is to link these performance parameters to a graph that supports schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We find 12 studies focusing G-EPO. We select 10 of them for detailed review, as the energy indicators used in the other two studies are only relevant to occupant comfort [18,19]. Although some studies changed layout boundary forms and dimensions like in [20], they are not analysed in this review, as their interior space layouts were not changed correspondingly.…”
Section: Literature Review On G-epomentioning
confidence: 99%
“…We find 12 studies focusing G-EPO. We select 10 of them for detailed review, as the energy indicators used in the other two studies are only relevant to occupant comfort [18,19]. Although some studies changed layout boundary forms and dimensions like in [20], they are not analysed in this review, as their interior space layouts were not changed correspondingly.…”
Section: Literature Review On G-epomentioning
confidence: 99%
“…On the other hand, researchers have been working on space layout design for decades [25,26]; however, they mainly focused on other design objectives rather than energy performance. These objectives include safety [27,28], logistics [29,30], efficiency [31,32], finance cost [33,34], occupant health and performance [35,36], view connection [37,38] and acoustics [39,40]. These two research domains, space layout design and energy-efficient building design, are shown in Figure 1.…”
mentioning
confidence: 99%